DINAMIKA PENERIMAAN DIRI DENGAN KESEPIAN PADA PRA LANSIA - Anggi Puspita Sari; Sri Nurhayati Selian (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The increase in life expectancy in Indonesia has led to a growing number of pre-elderly individuals facing various physical, social, and psychological changes. This study aims to understand the dynamics of self-acceptance and loneliness among pre-elderly individuals. A qualitative approach with a phenomenological method was used. The participants were 3 pre-elderly women aged 45–59 years selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation, and analyzed using Miles and Huberman’s thematic analysis technique. The results show that pre-elderly individuals with high self-acceptance tend to experience lower loneliness. They accept themselves positively, think optimistically, and maintain active social relationships. Conversely, those with low self-acceptance are more likely to feel lonely and isolated. Family social support strengthens self-acceptance and reduces loneliness. This study highlights that self-acceptance and social support play key roles in enhancing the psychological well-being of pre-elderly individuals. Keywords: self-acceptance; loneliness; pre-elderly; phenomenologyCambria